Secondary metabolites in ethanolic extract of leaves of Desmodium molliculum (Kunth) DC. (Manayupa) - Barreto, Danilo (2018)
The aim of this study was evaluate presence of flavonoids and saponins in alcoholic extracts of leaves of Desmodium molliculum HBK " manayupa " These metabolites was valuated with the aim of contributing to a better understanding of the chemical composition of this plant. The species was collected in the district of Baños del Inca City of Cajamarca, department of Cajamarca to 2776 meters. The phytochemical march revealed the presence of tannins, flavonoids, alkaloids and saponins in the alcoholic extract. Chromatographic analysis of the alcoholic extract using isoflavones genistein and daizein and vitexin flavonoid as reference standard revealed the probable presence of these isoflavonoids and the flavonoid in the alcohólic extract. UV spectroscopic analysis allowed us to confirm one of the isoflavone as genistein and 5-O-methylgenistein in addition chromatographic analysis using methanol extracts of defatted soybeans showed the probable presence of soyasaponins in the alcoholic extract.